Novel Evaluation Method for Site Effect on Earthquake Ground Motion Based on Modified Horizontal to Vertical Spectral Ratio - Li, Xiaojun; Li, Na; Rong, Mianshui; Dong, Qing (Frontiers in Earth Science, 2022)
The effect of local site conditions on the earthquake ground motion is a very important factor to be considered in engineering seismic fortification. Many methods, such as numerical simulation methods based on site analysis models and statistical empirical relation methods based on the earthquake ground motion observations and numerical simulation data, have been used to consider the site effects in actual engineering seismic fortification and earthquake disaster assessment. The statistical analysis to obtain characteristic parameters of site condition effect based on strong motion and microtremor records become an economical and practical method of determining the designed ground motion of engineering sites, especially for large survey areas and engineering sites where it is difficult to carry out a site survey. In this paper, a novel evaluation method for site effect on earthquake ground motion is proposed. The new method is based on the horizontal to vertical spectral ratio (HVSR) method, but the original HVSR is replaced by a modified HVSR considering the effect of the soil layer on the vertical ground motion. In order to build the model and determine the corresponding parameters of the modified HVSR, first, the ground motions in the bedrock below the soil layer are calculated using the one-dimensional equivalent linear method. These calculated records are independent of the influence of the downgoing wavefield, and the differences between the ground surface to bedrock spectral ratio (SBSR). The HVSR for the local sites of ground motion observation stations are analyzed using the strong ground motion records from the Kiban-Kyoshin network (KiK-net) in Japan. The statistical characteristics of the relationship between SBSR and HVSR are revealed, and then, a quantitative relationship between SBSR/HVSR and HVSR is established. The proposed evaluation method for the site effect has the advantage that the original HVSR method only requires ground motion records on the ground surface of the site, and it further considers the influence of the vertical seismic effect on the accuracy of the HVSR method. The proposed method can characterize the influence of the site conditions on ground motion more reasonably than the conventional method.